Bioflocos ex-situ e gema de ovo como alimento para Betta splendens - GIOVANNA RODRIGUES STRINGHETTA (2023)
The present work aims to evaluate the growth and survival of Betta splendens fingerlings fed with biofloc ex-situ and to evaluate the zootechnical and reproductive performance parameters of adult bettas fed with different levels of replacement of the ration by egg yolk. Betta is a species of fish with a carnivorous eating habit, prefers foods that move in the water, but adapts easily to ration. Taking into consideration the high cost of fish meal, which is an essential component in the manufacture of feed, and live foods (such as Artemia spp.), it is necessary to seek food alternatives that meet the nutritional requirements of the species. Bioflocs usually have a bromatological composition that meets the nutritional requirements of B. splendens, making this technology possible to be used for feeding this species. In addition, egg yolk has a composition of fatty acids that can be used for gamete production or energy storage during fish reproduction. Therefore, two experiments were conducted with Betta splendens to evaluate these possible substitute/complementary foods in the productive and reproductive performances of the species. In the first experiment, the fish received five different diets containing bioflocs (BFT), live food (LF100), and the combination of both foods, replacing the live food with the inclusion of bioflocs (LF100+BFT, LF85+BFT and LF70+BFT). Fish fed 15% less brine shrimp had higher final weight (P<0.05) but did not differ from those fed only brine shrimp. Fingerlings with greater final length (P<0.05) were observed in the LF100+BFT treatment. Survival was higher (P<0.05) in treatment LF100. Fish fed only BFT had the worst performance of the groups. Betta splendens supplemented with ex-situ bioflocs and live food reduction showed good performance and reinforce that ex-situ bioflocs can be used to reduce the use of live food, maintaining good development. In the second experiment, three treatments were adopted: only commercial feed (R100), replacement with 15% (R85) and with 30% (R70) egg yolk. Two reproductions occurred, with an interval of 30 days between them, being evaluated the reproductive performances of males and females. Females of all treatments did not spawn in the first reproduction; only the males built the nests. However, only females that received supplementation with egg yolk spawned in the second reproduction. The final weight of males was higher (P<0.05) in fish that received supplementation with 15% (2.56 g) and 30% (2.83 g) of egg yolk compared to fish that received only ration (1.95 g). The treatments with partial inclusion of egg yolk in the diet of Betta splendens were the only ones in which the females spawned, indicating that a partial replacement of ration by egg yolk can influence the reproduction of the species.